Coseismic and Postseismic Deformation of the 2016 Central Tottori Earthquake and its Slip Model. Issue 2 (27th February 2019) - Meneses‐Gutierrez, Angela; Nishimura, Takuya; Hashimoto, Manabu
Abstract: We analyze Global Navigation Satellite System (GNSS), Interferometric Synthetic Aperture Radar, and accelerometer data within the San‐in Shear Zone in order to clarify the coseismic and postseismic slip distributions associated with the M w 6.2 2016 Central Tottori earthquake. Inversion of the coseismic displacement data to estimate the slip distribution on the rupture fault shows a patch of large slip to the northwest of the hypocenter of the mainshock location. Relocated aftershocks and off‐fault seismicity 1 month after the mainshock are in agreement with stress change patterns caused by the mainshock fault. Inversion of near‐field GNSS displacements in 7 months following the earthquake under the assumption of afterslip does not show a preferred slip patch but rather a smooth distribution of the slip at shallow depths. Restricted slip propagation of afterslip on the 2016 event might suggest that inland faults in the San‐in Shear Zone are immature. Limited resolution of the GNSS data might inhibit us from finding the slip at depth. Key Points: Coseismic and postseismic slip distributions of the 2016 Central Tottori earthquake are retrieved from data inversion Coseismic slip is found northwest of the mainshock hypocenter over an 8‐km × 12‐km area, while afterslip is observed at shallow depths Restricted slip propagation in the postseismic period suggests immature faults in the San‐in Shear Zone